Unification and Planning of Urban Public Spaces With Bioclimatic Conditions. Case Study Drama, Greece - Julia Georgi; Sophia Sarikou (European Regional Science Association (ERSA), 2006)
The green spaces in the urban environment facilitate the movement of air masses that act as air refreshment in the wider region. The unification of urban open spaces and their enrichment with vegetation affect the micro-climate positively and act as a decisive factor for the increasing of urban thermal comfort, via the shading and the phenomenon of evapotranspiration. The planning of urban public spaces can support a habitat network encouraging the connectivity of the man-made environments with the surrounding natural ecosystems. The present paper aims to promote the unification of urban open spaces, with bioclimatic criteria by emphasizing the role of vegetation aiming the enhancement of living conditions in settlements. In particular is analysed the data collection like the proportion of building height with road width H/W, the road orientation and the solar access, the paving materials, the existent vegetation and concludes to an urban unification in a central part of Drama city in Northern Greece, by creating walkways and green corridors. The issue of solar access outdoors has been briefly discussed as an additional criterion in landscape designing the street. Design recommendations are also outlined for designing comfortable urban spaces.
Keywords: 330